Ladder Diagram based on State Diagram for Selection and Assembling Part on Dual Conveyor - Eka Iskandar; Mochammad Rameli; Nicco Nicco (Department of Electrical Engineering ITS and FORTEI, 2017)
In industry, conveyor is a means of transportation to move production materials. Conveyor not just move the goods but there are other processes such as counting the number of goods, filling the liquid and so forth because it is equipped with certain sensors and actuators. These processes can be automated by using PLCs as controllers by executing instruction programs in the form of ladder diagrams. The complexity of automation processes in conveyors requires the use of many relays in PLC programming and is difficult to apply to low-specification PLCs. Of course the procurement of PLC with high specifications require a lot of money. In order to overcome these problems it is necessary a method that can minimize the number of relays used so that the program becomes shorter. By using state diagram, the result of construction of ladder diagram is obtained by 32 rung and the program capacity is 3 KB.Keywords: Conveyor, Flow-Table/State Diagram, Ladder Diagram, PLC, Rung.